2016
DOI: 10.1002/ddr.21341
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Pharmacogenetics: Where Do We Stand?

Abstract: Preclinical Research Bipolar disorder (BPD) is a chronic and disabling psychiatric disorder with a prevalence of 0.8-1.2% in the general population. Although lithium is considered the first-line treatment, a large percentage of patients do not respond sufficiently. Moreover, lithium can induce severe side effects and has poor tolerance and a narrow therapeutic index. The genetics of lithium response has been largely investigated, but findings have so far failed to identify reliable biomarkers to predict clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 64 publications
0
33
0
3
Order By: Relevance
“…An alternative explanation may be that the effects of lithium are highly dependent on the ‘diseased’ genotype/phenotype. This goes along with the increasing body of evidence suggesting a key role of pharmacogenetics in the response to lithium (Pisanu et al, 2016a). Accordingly, different, more homogeneous phenotypes have been identified within patients regarding their likelihood of showing an adequate response to lithium treatment (responders vs. nonresponders) (Geoffroy et al, 2017; Oedegaard et al, 2016; Scott et al, 2017; Sportiche et al, 2016), and the genetic basis of lithium responsiveness has been consistently shown by several studies (Alda, 2015; Alda et al, 2005; Grof et al, 2009; Grof et al, 2002; Hou et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
“…An alternative explanation may be that the effects of lithium are highly dependent on the ‘diseased’ genotype/phenotype. This goes along with the increasing body of evidence suggesting a key role of pharmacogenetics in the response to lithium (Pisanu et al, 2016a). Accordingly, different, more homogeneous phenotypes have been identified within patients regarding their likelihood of showing an adequate response to lithium treatment (responders vs. nonresponders) (Geoffroy et al, 2017; Oedegaard et al, 2016; Scott et al, 2017; Sportiche et al, 2016), and the genetic basis of lithium responsiveness has been consistently shown by several studies (Alda, 2015; Alda et al, 2005; Grof et al, 2009; Grof et al, 2002; Hou et al, 2016).…”
Section: Discussionmentioning
confidence: 83%
“…These have been reviewed extensively elsewhere [21, 22]; only 2 will be briefly summarized here. First is lithium’s known inhibition of the protein GSK3β [2325].…”
Section: Archetypal Mediators Of Lithium’s Therapeutic Effectsmentioning
confidence: 99%
“…Li has wide efficacy to treat many neurological disorders, but the mechanism of action is debated (Pisanu et al, 2016). Several recent case studies suggest that Li has therapeutic potential for treating human Shankopathies (Darville et al, 2016;Egger et al, 2017;Serret et al, 2015), leading us to wonder whether Li might rescue the synaptic scaling defect induced by Shank3 loss.…”
Section: Synaptic Scaling Blockade Caused By Shank3 Kd Can Be Relievementioning
confidence: 99%